Novel Approaches for Targeting Metalloproteinases - Santamaria, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is a collection of eleven articles (five reviews and six studies) that describe a wide range of approaches to modulating metalloproteinase activity in disease. The techniques described are in vitro, in vivo, and ex vivo.